ChemInform Abstract: B‐Site Metal (Pd, Pt, Ag, Cu, Zn, Ni) Promoted La1‐xSrxCo1‐yFeyO3‐ δ Perovskite Oxides as Cathodes for IT‐SOFCs. Issue 31 (August 2015) - Guo, Shaoli; Wu, Hongjing; Puleo, Fabrizio; Liotta, Leonarda F.
Abstract Review: 77 refs.